2017
DOI: 10.15406/jmen.2017.05.00144
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole Resistance in Anaerobes Isolated from Patient with Oral and Maxillofacial Infections Attending Muhimbili National Hospital, Dar-Es-Salaam, Tanzania

Abstract: Background: Oro-facial infections, mostly bacterial infections, are among the most commonly encountered problems in the oral and maxillofacial surgical practice world over. These infections if not properly diagnosed and treated usually result in significant morbidity and are often fatal. The infection is caused by both aerobic and anaerobic microorganism where as treatment is given using broad spectrum antibiotics mostly common combination of Amoxicillin and Metronidazole. Metronidazole is commonly targeted dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This finding is in conflict with some studies which have found it effective in treating anaerobic infections including skin and soft tissues [ 52 ]. However, in Tanzania, metronidazole had a questionable activity in treating wound infection when compared to other studies, especially in bacteria isolated from the head and neck and other parts of the body [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in conflict with some studies which have found it effective in treating anaerobic infections including skin and soft tissues [ 52 ]. However, in Tanzania, metronidazole had a questionable activity in treating wound infection when compared to other studies, especially in bacteria isolated from the head and neck and other parts of the body [ 53 ].…”
Section: Discussionmentioning
confidence: 99%